distributions of a wide range of taxonomic groups are expanding polewards - Hickling, Rachael; Roy, David B; Hill, Jane K; Fox, Richard; Thomas, Chris D (Global change biology, 2006)
Evidence is accumulating of shifts in species' distributions during recent climate warming. However, most of this information comes predominantly from studies of a relatively small selection of taxa (i.e., plants, birds and butterflies), which may not be representative of biodiversity as a whole. Using data from less well-studied groups, we show that a wide variety of vertebrate and invertebrate species have moved northwards and uphill in Britain over approximately 25 years, mirroring, and in some cases exceeding, the responses of better-known groups.